2017
DOI: 10.18632/oncotarget.18699
|View full text |Cite
|
Sign up to set email alerts
|

NEURL4 regulates the transcriptional activity of tumor suppressor protein p53 by modulating its oligomerization

Abstract: p53 is a transcription factor that regulates important cellular processes related to tumor suppression, including induction of senescence, apoptosis, and DNA repair as well as the inhibition of angiogenesis and cell migration. Therefore, it is critical to understand the molecular mechanism that regulates it. p53 tetramerization is a key step in its activation process and the regulation of this oligomerization, an important control point. The E3 ubiquitin ligase HERC2 controls the p53 transcriptional activity b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 36 publications
(62 reference statements)
1
22
0
Order By: Relevance
“…The role of the HERC2-NEURL4 complex in activating the tumor suppressor p53 could explain the improved prognosis for cancer patients when levels of HERC2 expression are higher (Figure 1A). According to this model, NEURL4 should also function as a tumor suppressor and in agreement with this, analysis of cancer genomics datasets from the cBioPortal shows a high frequency in NEURL4 deletions in prostate cancer (10).…”
supporting
confidence: 63%
See 1 more Smart Citation
“…The role of the HERC2-NEURL4 complex in activating the tumor suppressor p53 could explain the improved prognosis for cancer patients when levels of HERC2 expression are higher (Figure 1A). According to this model, NEURL4 should also function as a tumor suppressor and in agreement with this, analysis of cancer genomics datasets from the cBioPortal shows a high frequency in NEURL4 deletions in prostate cancer (10).…”
supporting
confidence: 63%
“…The second model emerges from studies performed by Cubillos-Rojas et al (9, 10). Those authors demonstrate how HERC2 regulates p53 activity.…”
mentioning
confidence: 99%
“…Assembly of protein components is an important theme in transcriptional regulation (45)(46)(47). A central element of this process is often the oligomerization of one or more individual protein components contributing to transcriptional complex assembly (27,28). In the case of CtBP, strong evidence exists for the role of NAD(H) in both co-transcriptional activity and oligomerization (3,23,25,29,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of gene expression through the oligomerization of transcriptional factors is an important paradigm (27,28). In the case of CtBP, substantial evidence exists that oligomerization is linked with NAD(H) binding (3, 25, 29 -32), and dimerdestabilizing mutants have been found to inhibit transcriptional function (33)(34)(35)(36).…”
mentioning
confidence: 99%
“…For example, HERC2 controls the transcriptional activity of the tumor suppressor protein p53 [66]. Tetramerization of p53 is a key step in its activation, and this oligomerization process is modulated by a complex formed by NEURL4 and HERC2 [67]. Recently, it has been reported that MDM2 is present in this complex.…”
Section: Regulation Of P53 Transcriptional Programmingmentioning
confidence: 99%